BIBLICAL IDIOMS WITH SOMATISMS IN THE PHRASE TRIADA - MYKHAYLENKO, Valeriy (Науковий вісник Ужгородського університету. Серія Філологія, 2020)
Our hypothesis is that the biblical unit structurally and semantically indecomposable and meets the charac- teristics of the idiom. And the assumption is based on the critical analysisof numeroues definitions and classifications of each constituent of the triad in the language system and the language in-use [cf. Boye 2019]. (i)The term phrase is defined as one or more words functioning as a unit in a sentence. The premodial concept—one or more is false: as the head word and adjunct are obligatory members of the phrase. (ii)The definition that a phrase is any group of words which are taken to be less than a sentence is not correct because non-sensical words can be also grammtically corect.(iii) The phrase is a group of two or more words functioning as a meaningful unit within a sentence or clause though a phrase is commonly characterized as a grammatical unit at a level between a word and a clause [see also Borsley 1996]. The phrase is a syntactic structure that contains one or more words but does not contain both a subject and a verb. The use of ”one word”in the definition makesthis definition also dubious. Wе understand that idioms and phraseological units do have some distinctions and a superfine operation can separate and secure them from their transformation into Yin and Yang as opposites. And the scholar must search for a precision instrument to separate this concept further on. In linguistics it is is the corpora analysis can provide us with nunerous samples and their frequency is a crucial point in separating idioms from phraseologisms which can be verified in the process of the discourse analysis. Our assumption is the idioms are the feature of colloquial style, social dialects, language varietis, professional discourse. The evolution of the units through the stages: from the free syntactical phrase through the fixed syntactical phrases and then to idioms, first professiionally marked and then their further penetration into the standard literary language use must be crowned with the status of a phraseological unit characteristic of the a literary standard. Somatic idioms constitute a significant part of biblical idioms and can be compared with thosefunctionin in variousprofessional discourse registers.